(untitled) (European Journal of Health Research, 2015)
Madica II © study. To contribute to improve the management of the elderly diabetic patients MADICA © Study was designed, which aim is to determine the degree of therapeutic inertia (IT) in those over 65 Type 2 Diabetes Mellitus patients, after an intervention done to healthcare professionals and patients. A cross-sectional retrospective study in MADICA I © , and a cohort design, MADICA II © .The intervention group belongs to “La Laguna”, and the control one to “Loreto-Puntales”, N=570. Patients’clinical histories were reviewed, analizyng social-demographic, clinical, biochemical, pharmacological, geriatric evaluation and IT variables. In MADICA I © Study, the whole IT is 81.58%, 60.86% belongs to “La Laguna”, being MIR 58.79% and no MIR 72.81%; the IT in “Loreto-Puntales” is 91.23%, being MIR 92.25%, and no MIR 90.83%. After the intervention, MADICA II © , the whole IT is 72.98%, the IT in “La Laguna” is 58.39%, being MIR 51.69% and no MIR 70.83%; the IT in “Loreto Puntales” is 88.17%, being MIR 89.92%, and no MIR 86.67%. The degree of IT in the elderly diabetics of Cadiz is high. Previous training academic level, joint to a continuous training in diabetes and Geriatrics is an essential step to reduce IT.